2020
DOI: 10.1016/j.thromres.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological and obstetric outcome in the French cohort of women with factor XIII deficiency

Abstract: Introduction: Congenital factor XIII deficiency is a very rare bleeding disorder affecting 33 patients in France. Besides its role in fibrin clot stabilization, factor XIII is involved in placental attachment. Fetal miscarriages represent a frequent and concerning issue for these patients. The aim of the present study was to describe clinical characteristics of women presenting severe congenital FXIII deficiency in France, to focus on gynecological and obstetrical events, and to report the management of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
12
0
2
Order By: Relevance
“…Regarding miscarriages, Sharief et al report that, in 121 women with FXIIID, the risk of miscarriages was very high, nearly 70% [20]. Without FXIII substitution, the frequency of pregnancy with birth of a healthy infant was estimated to be 10%, and miscarriages occurred mainly during the first trimester [20]; a high risk of miscarriage was also the main feature of pregnancies in women with FXIIID in the French study: 30 miscarriages in 4 patients, including 12 in one patient who did not receive FXIII substitution before or during pregnancies [21], and 97% of these miscarriages occurred during the first trimester. These results are similar to those published by Naderi et al who reported 17 cases in Iran [7].…”
Section: Prevalence and Clinical Manifestations Of Fxiii Deficiencymentioning
confidence: 94%
See 4 more Smart Citations
“…Regarding miscarriages, Sharief et al report that, in 121 women with FXIIID, the risk of miscarriages was very high, nearly 70% [20]. Without FXIII substitution, the frequency of pregnancy with birth of a healthy infant was estimated to be 10%, and miscarriages occurred mainly during the first trimester [20]; a high risk of miscarriage was also the main feature of pregnancies in women with FXIIID in the French study: 30 miscarriages in 4 patients, including 12 in one patient who did not receive FXIII substitution before or during pregnancies [21], and 97% of these miscarriages occurred during the first trimester. These results are similar to those published by Naderi et al who reported 17 cases in Iran [7].…”
Section: Prevalence and Clinical Manifestations Of Fxiii Deficiencymentioning
confidence: 94%
“…In the French study previously mentioned, 11 pregnancies conducted under the administration of pdFXIII doses ranging from 400 to 800 IU per week throughout the pregnancy had a good outcome [21]; and increasing doses were prescribed during 3 pregnancies. These results suggest that at least one infusion of 400 IU per week of pdFXIII could lead to safe child birth [21].…”
Section: Treatment Options For Gynecological and Obstetric Complications In Womenmentioning
confidence: 99%
See 3 more Smart Citations